Strategist on the Board - Pettigrew, A; McNulty, T (1999)
The paper examines the contribution to strategy by chairmen and non-executive directors in large UK companies. The collective label of `part-time board member' is used to refer to individuals performing these roles. The paper asks `how, if at all, do part-time board members influence strategy in UK plc's'?. Using data gathered from interviews with 108 company directors, the paper suggests that part-time board members do not simply ratify decisions made by all-powerful executives. A conceptual model is developed to show that part-time board members are able to influence processes of strategic choice, change and control by shaping both the ideas that form the content of company strategy and the methodologies and processes by which those ideas evolve. Their involvement in strategy is conditioned by factors such as: changing norms about corporate governance; the history and performance of the company; the process and conduct of board meetings and informal dialogue amongst company directors between board meetings.